Biochip-based study of unidirectional mitochondrial transfer from stem cells to myocytes via tunneling nanotubes. (4th February 2016) - Yang, Huaxiao; Borg, Thomas K; Ma, Zhen; Xu, Meifeng; Wetzel, George; Saraf, Laxmikant V; Markwald, Roger; Runyan, Raymond B; Gao, Bruce Z
Abstract: Tunneling nanotubes (TNTs) are small membranous tubes of 50–1000 nm diameter observed to connect cells in culture. Transfer of subcellular organelles through TNTs was observed in vitro and in vivo, but the formation and significance of these structures is not well understood. A polydimethylsiloxane biochip-based coculture model was devised to constrain TNT orientation and explore both TNT-formation and TNT-mediated mitochondrial transfer. Two parallel microfluidic channels connected by an array of smaller microchannels enabled localization of stem cell and cardiomyocyte populations while allowing connections to form between them. Stem cells and cardiomyocytes were deposited in their respective microfluidic channels, and stem cell-cardiomyocyte pairs were formed via the microchannels. Formation of TNTs and transfer of stained mitochondria through TNTs was observed by 24 h real-time video recording. The data show that stem cells are 7.7 times more likely to initiate contact by initial extension of filopodia. By 24 h, 67% of nanotube connections through the microchannels are composed of cardiomyocyte membrane. Filopodial extension and retraction by stem cells draws an extension of TNTs from cardiomyocytes. MitoTracker staining shows that unidirectional transfer of mitochondria between stem cell-cardiomyocyte pairs invariably originates from stem cells. Control experiments with cardiac fibroblasts and cardiomyocytes show little nanotube formation between homotypic or mixed cell pairs and no mitochondrial transfer. These data identify a novel biological process, unidirectional mitochondrial transfer, mediated by heterotypic TNT connections. This suggests that the enhancement of cardiomyocyte function seen after stem-cell injection may be due to a bioenergetic stimulus provided by mitochondrial transfer.